Moral and political philosophy : key issues, concepts and theories - Smith, Paul, 1953- (Palgrave Macmillan, 2008)
This text provides a comprehensive examination of key concepts and theories in moral and political philosophy. With a clear focus on the essentials of each topic, Smith presupposes no prior knowledge and relates moral philosophy to social and political issues.